2018
DOI: 10.1021/jacs.8b04679
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Imaging of Clickable Graphene Nanoribbons Decorated with Fluorescent Dyes

Abstract: The functional integration of atomically defined graphene nanoribbons (GNRs) into single-ribbon electronic device architectures has been limited by access to nondestructive high-resolution imaging techniques that are both compatible with common supports such as Si or Si/SiO wafers and capable of resolving individual ribbons in dilute samples. Conventional techniques such as scanning probe (AFM, STM) or electron microscopy (SEM, TEM) have been restricted by requisite sample preparation techniques that are incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Composite electrodes comprising gold nanoparticles and the synthesized GNRs displayed a synergistic performance enhancement for the electrocatalytic reduction of CO 2 . Thereafter, Fischer and Xu et al [247] reported GNR 185 decorated with fluorescent dyes along the edges for super-resolution imaging. The synthesis relied on a key GNR 184 featuring pendant azide groups, which was used to attach the dye molecules by the copper-catalyzed azide-alkyne cycloaddition (CuAAC click reaction) (Figure 37(c)).…”
Section: Edge Functionalizationmentioning
confidence: 99%
“…Composite electrodes comprising gold nanoparticles and the synthesized GNRs displayed a synergistic performance enhancement for the electrocatalytic reduction of CO 2 . Thereafter, Fischer and Xu et al [247] reported GNR 185 decorated with fluorescent dyes along the edges for super-resolution imaging. The synthesis relied on a key GNR 184 featuring pendant azide groups, which was used to attach the dye molecules by the copper-catalyzed azide-alkyne cycloaddition (CuAAC click reaction) (Figure 37(c)).…”
Section: Edge Functionalizationmentioning
confidence: 99%
“…Raman spectra of CHO-cGNRs show the characteristic signatures of cGNRs; a radial breathing like mode (RBLM) (253 cm -1 ), the D (1332 cm -1 ), and the G (1603 cm -1 ) peaks as well as overtone 2D, D+D ' , and 2D ' peaks ( Fig. 1D) 20,22,23 . An overlay of the respective IR spectra of poly-phenylene 5 and CHO-cGNR confirms the presence of aldehyde groups in the GNRs.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…The synthesis of GNRs can be modified for incorporation of functional substituents to build in chromophores or stable free radicals, which will be useful later. [146][147][148][149][150] Additionally, GNRs can be subjected to further transformations by employing chlorination 58 and potentially hydrogenation, 151 as already established for NGs. Regarding scalability, the abovedescribed synthesis has been performed on a gram scale and can certainly be developed for even larger quantities.…”
Section: Faraday Discussion Accepted Manuscriptmentioning
confidence: 99%